Effect of Effective Tax Rate, Tunneling Incentive, and Bonus Mechanism on Transfer Pricing Decision - Herlina Herlina; Sitti Murniati (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
This study examines the impact of the effective tax rate, tunneling incentive, and bonus method on transfer pricing decisions. This study focuses on the population of manufacturing companies in the primary and chemical industries listed on the Indonesia Stock Exchange. The period of this study is from 2018 to 2022, which includes 70 companies. The sample size consists of 11 companies selected using the purposive sampling method. The data source consists of secondary data, specifically financial reports from manufacturing companies listed on the IDX (Indonesia Stock Exchange). The time selected for data collection covers 2018 to 2022. This study uses a Panel Data regression approach. This research also uses various ways to look at the data, such as descriptive statistics, normality tests, heteroscedasticity tests, multicollinearity test, autocorrelation tests, hypothesis testing with coefficient of determination test, partial test, and simultaneous tests. The preliminary findings show that the effective tax rate positively and statistically significantly influences transfer pricing decision-making. The existence of tunneling incentives and bonus mechanisms is found to have a statistically insignificant impact on transfer pricing decisions. The bonus mechanism has an adverse and substantial effect on the decision-making process related to transfer pricing.